The impact of sex on blood pressure and anthropometry trajectories from early adulthood in a Nigerian population: insights into women's cardiovascular disease risk across the lifespan - Oluseyi Adegoke; Oluwadamilola O. Ojo; Obianuju B. Ozoh; Ayesha O. Akinkugbe; Ifedayo A. Odeniyi; Babawale T. Bello; Osigwe P. Agabi; Njideka U. Okubadejo (BMC, 2022)
Abstract Background Sex disparities in blood pressure and anthropometry may account for differences in cardiovascular (CV) risk burden with advancing age; modulated by ethnic variability. We explored trajectories of blood pressures (BPs) and anthropometric indices with age on the basis of sex in an urban Nigerian population. Methods We conducted a secondary analysis on data from 5135 participants (aged 16-92 years; 2671(52%) females) from our population-based cross-sectional study of BP profiles. We utilized the WHO STEPS and standardized methods for documenting BPs, body mass index (BMI) and waist circumference (WC). Data was analyzed using Analysis of variance (ANOVA), Spearman correlation analysis and mean difference in variables (with 95% confidence interval). We explored the influence of age and sex on BP profiles and specific anthropometric indices using generalized regression analysis. Results In those aged 15-44 years, males had significantly higher systolic BP (SBP) and pulse pressure (PP). However, mean SBP and PP rose more steeply in females from 25 to 34 years, intersected with that of males from 45 to 54 years and remained consistently higher. Difference in mean BPs (95% Confidence Interval) (comparing < and > 45 years) was higher in females compared to males for SBP (17.4 (15.8 to 19.0) v. 9.2 (7.7 to 10.7), DBP (9.0 (7.9 to 10.1) v. 7.8 (6.7 to 8.9)), and PP (8.4 (7.3 to 9.5) v. 1.4 (0.3 to 2.5)). Females had significantly higher BMI and WC across all age groups (p < 0.001). Age more significantly correlated with BPs, BMI and WC in females. Interaction models revealed that SBP was significantly predicted by age category in females from (15-54 years), while DBP was only significantly predicted by age in the 15-34-year category (p < 0.01). BMI and WC were significantly predicted by age only in the 25-34-year category in females, (p < 0.01). Conclusions Our population demonstrates sex disparity in trajectories of SBP, PP, BMI and WC with age; with steeper rise in females. There is a need to focus on CV risk reduction in females, starting before, or during early adulthood.